Wayang Sukuraga Dari Bahasa Rupa ke Bahasa Pertunjukan - Alief Suardi (Pascasarjana ISBI Bandung, 2019)
Wayang Sukuraga has initially been performed to the public since 1997. Generally, the story of Wayang Sukuraga is different from the common Wayang whose stories are inspired from Ramayana and Mahabrata. The names of the characters of Wayang Sukuraga are taken from part of bodies, such as, mouth, eye, ear, nose, hand, foot. The stories focus on telling internal conflict of human from their bodies. The research is aimed to reveal the meaning and symbol on Wayang Sukuraga. This is a qualitative study applying Levi-Strauss theory in analyzing the concept of structure and transformation. The result of the study shows that Wayang Sukuraga wants to share the understanding on how the human part of bodies fight and handle their desires. One of the creators, Effendy, has multi interpretation toward the characters in Wayang Sukuraga. The interpretations are an argumentation based on the phenomena in the daily life. The interpretation is easily understood by the human who have bodies.Keywords: Sukuraga, Wayang Sukuraga, Contemporary, Effendy